Histopathological Study of Cystoscopic Bladder Biopsies in a Tertiary Care Center - Dhakal, Rachana; Joshi, Hem Nath; Makaju, Ramesh; Sigdel, Shailendra (Birat Journal of Health Sciences, 2021)
Introduction: Non-neoplastic urinary bladder lesions are not life threatening, but are an important source to cause clinical symptoms and signs. However, neoplasms of the bladder are a source of morbidity, mortality, and exhibit more clinical challenges. Cystoscopy provides overall information about an anatomical/pathological condition of the urinary bladder which will be helpful for patients' management. A cystoscopic biopsy is a primary diagnostic tool for diagnosing urinary bladder cancer.Objectives: The objective of the study was to find the frequency and histomorphological characteristics of urinary bladder lesions in Dhulikhel Hospital, to find the clinical presentation of urinary bladder lesions and to grade the urothelial tumors based on the World Health Organization (WHO)/ International Society of Urological Pathology (ISUP) classification 2004.Methodology: This was a retrospective, cross-sectional, observational study carried out in the Department of Pathology, Dhulikhel Hospital-Kathmandu University Hospital. Convenient sampling was done. All cystoscopy biopsies received from January 2014 to December 2018 were studied. All tissue blocks were retrieved, cut, and stained with Hematoxylin and Eosin. The stained slides were examined under a light microscope by the primary investigator.Result: A total of 70 cystoscopic biopsies were analyzed. The majority of patients 20 (28.6%) were in the age group between 60 and 69 years and males were predominant 43 (61.4%). The neoplastic lesions constituted 40 (57.1%) of all bladder lesions, among them urothelial carcinoma accounted for 38 (54.2%). Similarly, chronic cystitis 27(38.6%) was the most common non-neoplastic lesion.Conclusion: The study found that the neoplastic lesions were commonly encountered in urinary bladder lesions. Among them, lowgrade urothelial carcinoma was the most common bladder tumor. However, most of the non-neoplastic lesions were inflammatory in origin. Cystoscopy combined with histomorphological examination helps in the early detection of bladder lesions.